5(7x-3)=-10(-2x+1)

Simple and best practice solution for 5(7x-3)=-10(-2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(7x-3)=-10(-2x+1) equation:


Simplifying
5(7x + -3) = -10(-2x + 1)

Reorder the terms:
5(-3 + 7x) = -10(-2x + 1)
(-3 * 5 + 7x * 5) = -10(-2x + 1)
(-15 + 35x) = -10(-2x + 1)

Reorder the terms:
-15 + 35x = -10(1 + -2x)
-15 + 35x = (1 * -10 + -2x * -10)
-15 + 35x = (-10 + 20x)

Solving
-15 + 35x = -10 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
-15 + 35x + -20x = -10 + 20x + -20x

Combine like terms: 35x + -20x = 15x
-15 + 15x = -10 + 20x + -20x

Combine like terms: 20x + -20x = 0
-15 + 15x = -10 + 0
-15 + 15x = -10

Add '15' to each side of the equation.
-15 + 15 + 15x = -10 + 15

Combine like terms: -15 + 15 = 0
0 + 15x = -10 + 15
15x = -10 + 15

Combine like terms: -10 + 15 = 5
15x = 5

Divide each side by '15'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| -6+27+(-70)= | | 5r^2=35r | | 5(f-8)=-40 | | 3x+12=28-5x | | 1-8x=-16x^2 | | 2b-c-a+4=0 | | 3+7lnx=38 | | 2b-a-c+4=0 | | -10(s+5)=-133 | | 2a-b-c+4=0 | | 7+12x=29+x | | -49=-2x+3(-2x+13) | | -10(s+5)=133 | | 54n^3-2000=0 | | -3x^2+6x=4 | | t-(-2)=-8 | | b+2c-4a+2=0 | | b+2a-4c+2=0 | | 4.2/3-1 | | 6(t+2)=0 | | 2(2b+6)=4b-8 | | 7|-1-3|= | | 5-3(3+5x)=71 | | 169=37x-16 | | -6+9-(-7)= | | -16x^2+144x=0 | | 6x-8=4x+22 | | y-9=-2/3x | | 1-7/5x3 | | 3/7-0 | | 2x=111 | | 4(a-2)=6(a+15) |

Equations solver categories